Critical Analysis of the Frequency and Factors Leading to Hypocalcemia after Total/ Near Total Thyroidectomy - Marvi Sangi, Aisha Shaikh, Saira Fatima, Nadia Bhatti, Muharam Ali, Aasia Aamir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To critically analyze the frequency and factors leading to hypocalcemia in Total/ Near Total thyroidectomy Methods: This descriptive case series study was conducted over period of one year by taking sample of 138 patients of simple multinodular goiter or carcinoma of thyroid who underwent total/near total thyroidectomy and patients who had serum calcium <8mg/dl postoperatively. Recurrent thyroid surgery or patients undergoing lobectomy were excluded from the study. SPSS version 21 was used for data analysis. Mean ± SD represent the continuous variables & frequencies/ percentages represent the quantitiave results. Chi-square test was applied to analyze effect modification. P value <0.05 was taken as significant. Study was approved by the ethical review committee of the SMBBMU - Larkana. Results: The mean ± SD age of patients was 39.86 ± 11.5 years with a range from 22 to 60 years. The mean ± SD serum Pre-operative calcium was 9.64 ± 0.44 mg/dL. Post thyroidectomy) values of serum calcium were noted as mean ± SD 7.68 ± 2.11 mg/dL. Sixty five percent (n =90) of all patients were females. NTT- were 67.4% (n = 93) while TT- 32.6% (n = 45). Frequency of hypocalcemia was 28.3% (n = 39). More patients after TT developed hypocalcemia (44.4%) than NTT (20.4%) P value = 0.004). Old age, female gender, surgery for thyroid cancer and patient with lower preoperative serum calcium had a higher frequency of hypocalcemia after thyroidectomy. Practical implication Conclusion:The frequency of post thyroidectomy hypocalcemia in this study is 28.3%. Post thyroidectomy hypocalcemia is associated with both NTT and TT, however the frequency is more common (more than twice) after TT. Factors like old age, female gender, patients having thyroid cancer and having lower serum calcium preoperatively are strong effect-modifiers. Keywords: Total thyroidectomy. Near total thyroidectomy,Calcium, Hypocalcemia, .Parathyroid hormone.